Influence of Pellet Compaction Pressure on the Physical Properties of La0.7Ba0.3MnO3 Manganite - Freitas,Cintia Raquel Duarte de (2018)
Perovskite manganite La0.7Ba0.3MnO3, synthesized by ionic coordination reaction method (ICR) was compacted into pellets under different compaction pressures (Pc) and sintered at a temperature of 1150°C for 10h under a flow of O2. X-ray diffraction (XRD) data reveal that the samples can present simultaneously two phases - a rhombohedral structure with space group R3c and an orthorhombic structure with space group Pnma. Scanning electron microscopy (SEM) images show that, for this sintering temperature, the particle size and shape can be modified depending on the compaction pressure (Pc). Magnetization measurements show that the saturation magnetization and Curie temperature increase with Pc. The enhancement of the ferromagnetic properties of perovskite manganites La0.7Ba0.3MnO3 as a function of the compaction pressure is explained by an increase in the rhombohedral/orthorhombic structure ratio caused by this effect.